IMPROVING STUDENTS’ READING ABILITY USING SCHOOLOGY (AN ACTION RESEARCH OF THE 3rd SEMESTER IN ACADEMIC YEAR 2020/2021 OF STBA JIA, BEKASI) - Esterria Romauli Panjaitan; Winda Lutfiyanti; Inta Masni Sinaga (Wiralodra English Journal, 2023)
The research aimed to improve students’ reading by using Schoology e-learning. With 27 students as participants, this research used classroom action research method (planning, action, observing and reflecting) and descriptive analysis techniques to present the results of students' test. In cycle I, the writers claimed that some students were paying attention when lecturer taught them, responding to questions, and finishing classwork and homework. Meanwhile, several problems appeared because the other students were late to submit, passive in discussion, and difficult to follow Schoology instruction along with the unstable internet connection or unavailable quota. Besides, the writers neither give them motivation in each meeting nor review the previous lesson and give feedback to their results of learning. The students’ score improved from 65 (pre-test) to 69 (post-test) even under the target specified. In cycle II, students were more enthusiastic to follow the learning process. They were able to finish the classwork/homework in Schoology on time. The writers were always giving motivation and trying to do their best so that the students could achieve their targets or the improvement in reading. The mean score of post-tests in cycle II (74,8) showed that reading using schoology seemed to run effectively.